2015
DOI: 10.1007/s12975-015-0412-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral and Imaging Correlates of Hippocampal Atrophy in a Mouse Model of Vascular Cognitive Impairment

Abstract: Vascular cognitive impairment (VCI) is the second most common cause of dementia. Reduced cerebral blood flow is thought to play a major role in the etiology of VCI. Therefore, chronic cerebral hypoperfusion has been used to model VCI in rodents. The goal of the current study was to determine the histopathological and neuroimaging substrates of neurocognitive impairments in a mouse model of chronic cerebral hypoperfusion induced by unilateral common carotid artery occlusion (UCCAO). Mice were subjected to sham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 18 publications
(42 reference statements)
8
49
1
Order By: Relevance
“…A remarkably positive correlation between hippocampal integrity and spatial cognitive functions has been confirmed by previous studies [29, 30]. The significantly improved spatial learning and memory observed in the Morris water maze led us to suspect that there might be more intact hippocampal neurons in post-ischemic mice receiving n-3 PUFAs.…”
Section: Resultssupporting
confidence: 73%
“…A remarkably positive correlation between hippocampal integrity and spatial cognitive functions has been confirmed by previous studies [29, 30]. The significantly improved spatial learning and memory observed in the Morris water maze led us to suspect that there might be more intact hippocampal neurons in post-ischemic mice receiving n-3 PUFAs.…”
Section: Resultssupporting
confidence: 73%
“…Several rodent models of VaD have been developed, most of which rely on induction of chronic cerebral hypoperfusion to induce VaD‐related pathology (Jiwa, Garrard, & Hainsworth, ). In mice, UCCAo model has been previously used to produce a variety of VaD pathologies including white matter damage, inflammation, neuronal degeneration, and cognitive deficits (Bink, Ritz, Aronica, van der Weerd, & Daemen, ; Yoshizaki et al, ; Zhao et al, ; Zuloaga et al, ). At 30 days following UCCAo, LCN2 expression was induced in hippocampal astrocytes, similar to that of the tBCCAo animal model (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…The capability of improving long-term neurofunctional outcomes after stroke is imperative for a potential therapy to be translated from bench to bedside [3033]. Our recent study revealed beneficial effects of post-stroke DHA injections combined with FO dietary supplementation against stroke-induced cognitive decline [25].…”
Section: Resultsmentioning
confidence: 99%